Matcha tea: Molecular mechanisms and cardiovascular risk reduction. A literature review. - González-Londoño, Sofía (2022)
Aim: To establish the relationship between consumption of matcha tea and its benefits in reducing cardiovascular risk by recognizing the different molecular pathways and physiological mechanisms on which this compound and its metabolic agents may intervene, based on an analysis of the published literature. Materials and methods: A search for MeSH terms was carried out through the MeSH database, obtaining search terms such as “green tea”, “Green tea”, “Matcha tea”, “Tea Matcha”, “Matcha tea and cardiovascular risk”, “Matcha tea and cardiovascular risk ”from which a systematic search was carried out in databases such as Medline, Google Academic and Scielo, obtaining articles published between 2007 - 2021, written in Spanish and English and that were original articles and systematic reviews of Literature. Results: The articles reviewed had as a common purpose the study of the bioactive components of matcha green tea and the relationship that exists in terms of the prevention of CVD risk, especially of flavonoids and catechins, supporting the regular consumption of this drink as a potential method for the prevention of cardiovascular diseases, through various mechanisms of action such as antioxidant potential and the impact on the course of atherosclerotic activity, its protective role against injuries caused by ischemia / reperfusion, and the impact of these in reducing inflammation, benefits of these components, conferring a high value in the prevention of CVD to matcha green tea. Conclusions: According to the articles included in this review, it was possible to show that there is a direct relationship between matcha green tea and the reduction of cardiovascular risk, this due to the multiple benefits such as body weight reduction, reduction of cholesterol levels and reduction of injury caused by free radicals that have catechins and flavonoids, the main components of green tea.